The Geography of Job Creation and Job Destruction - Moritz Kuhn; Iourii Manovskii; Xincheng Qiu (Institute of Labor Economics (IZA), 2021)
Spatial differences in labor market performance are large and highly persistent. Using data from the United States, Germany, and the United Kingdom, we document striking similarities in spatial differences in unemployment, vacancies, job finding, and job filling within each country. This robust set of facts guides and disciplines the development of a theory of local labor market performance. We find that a spatial version of a Diamond-Mortensen-Pissarides model with endogenous separations and on-the-job search quantitatively accounts for all the documented empirical regularities. The model also quantitatively rationalizes why differences in job-separation rates have primary importance in inducing differences in unemployment across space while changes in the job-finding rate are the main driver in unemployment fluctuations over the business cycle.
Keywords: J63; J64; E24; E32; R13; 330; local labor markets; unemployment; vacancies; search and matching